Mecenato esportivo: o trajeto da Lei Federal de Incentivo ao Esporte em Belo Horizonte - Rafael Silva Diniz (2016)
The Federal Constitution of 1988 stood out the inclusion of sport in the list of social rights which form the Brazilian citizenship. The years that followed after the promulgation of Art. 217 was discussion in order to elaborate a general rule for sport and state restructuring the social element. Only with the approval of Lei Pelé (Law N.º 9,615/1998) and creation of the Ministry of Sport (2003), the sector was organized for the genesis of a public financing policy to all manifestations of the sport. The example of Lei Sarney (Law N.º 7,505/1986) and Lei Rouanet (Law N.º 8,313/1991), which sought to bring the cultural institution of the private sector, stimulating the figure of the cultural mecenas, through the tax incentive, it was also considered appropriate for the sports sector. Thus, at the end of 2006 it was approved in the National Congress the Lei Federal de Incentivo ao Esporte (Law N.º 11,438/2006). The experience in the culture already announced possible problems that sports patronage (mecenato) mechanism could face in its execution, due to the reality of economic inequalities and knowledge in the country. After almost ten years of the promulgation of the Lei Federal de Incentivo ao Esporte (Law N.º 11,438/2006) there are few academic studies which seek understanding operation and the impact on resource distribution. For that, it was necessary to draw a general picture, but nationwide, from the sports patronage (mecenato) from 2007 to 2015, for, in a second moment, deepening the path of this resource, claimed by the sports institution based in Belo Horizonte. For municipal research was used as snip time the 83 projects presented and 32 approved in 2013, being consolidated as information in analysis categorie. Several concentration problems of resource in geographic region and sports manifestation, influenced directly for the concentration in a little group of proponent, observed at a national level, also reproduced in Belo Horizonte territory.